2021
DOI: 10.5398/tasj.2021.44.2.160
|View full text |Cite
|
Sign up to set email alerts
|

The Performance, Nutrient Digestibility, Aflatoxin B1 Residue, and Histopathological Changes of Broilers Exposed to Dietary Mycosorb

Abstract: Aflatoxin B1 (AFB1) is the most dangerous type of aflatoxin that can impair poultry productivity even in low concentrations. The harmful effects of AFB1 should be minimized. The present study was conducted to evaluate the performance, nutrient digestibility, AFB1 residue, and histopathological changes of broilers fed AFB1 diets supplemented with mycosorb. Two hundred-forty 1-day old broiler chicks were allocated randomly to 24 pens (10 birds/pen). The experimental design was a 4 x 2 factorial arrangement, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to Negash (2018), there are six types of aflatoxin, involving aflatoxin B1, B2, G1, and G2, M1 (a metabolite of B1), and M2. Among all types of aflatoxin, aflatoxin B1 (AFB1) is the most dangerous type of aflatoxin, which can cause several harmful effects in humans and animals, such as enlarged liver, liver cancer, and hepatitis B virus infection (Nalle et al 2021;Benkerroum 2020). In addition, Nalle et al (2021) also reported that even at the low level, the AFB1 reduced the fat digestibility and feed efficiency, and changed the liver color.…”
Section: Effect Of Mold Inhibitor On Aflatoxin Content Of Cornmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Negash (2018), there are six types of aflatoxin, involving aflatoxin B1, B2, G1, and G2, M1 (a metabolite of B1), and M2. Among all types of aflatoxin, aflatoxin B1 (AFB1) is the most dangerous type of aflatoxin, which can cause several harmful effects in humans and animals, such as enlarged liver, liver cancer, and hepatitis B virus infection (Nalle et al 2021;Benkerroum 2020). In addition, Nalle et al (2021) also reported that even at the low level, the AFB1 reduced the fat digestibility and feed efficiency, and changed the liver color.…”
Section: Effect Of Mold Inhibitor On Aflatoxin Content Of Cornmentioning
confidence: 99%
“…Among all types of aflatoxin, aflatoxin B1 (AFB1) is the most dangerous type of aflatoxin, which can cause several harmful effects in humans and animals, such as enlarged liver, liver cancer, and hepatitis B virus infection (Nalle et al 2021;Benkerroum 2020). In addition, Nalle et al (2021) also reported that even at the low level, the AFB1 reduced the fat digestibility and feed efficiency, and changed the liver color. Thus, it is important to minimize the adverse effect of AFB1 in poultry feed ingredients.…”
Section: Effect Of Mold Inhibitor On Aflatoxin Content Of Cornmentioning
confidence: 99%
“…AFB1 has been the subject of regulation in food and feed in many countries [18] [19]. In addition, it is the most dangerous aflatoxin type that can impair poultry productivity even in low concentrations [20]. Scientific nomenclature for…”
Section: Introductionmentioning
confidence: 99%